Pain and stress assessment after retinopathy of prematurity screening examination: Indirect ophthalmoscopy versus digital retinal imaging - Moral-Pumarega M; Caserío-Carbonero Sonia; De-; Tejada-Palacios Pilar; Lora-Pablos David; Pallás-Alonso Carmen R (BMC, 2012)
Abstract Background Increasingly, neonatal clinics seek to minimize painful experiences and stress for premature infants. Fundoscopy performed with a binocular indirect ophthalmoscope is the reference examination technique for screening of retinopathy of prematurity (ROP), and it is associated with pain and stress. Wide-field digital retinal imaging is a recent technique that should be evaluated for minimizing infant pain and stress. Methods The purpose of the study was to assess and compare the impact of using a binocular indirect ophthalmoscope (BIO), or wide-field digital retinal imaging (WFDRI) on pain and stress in infants undergoing ROP screening examination. This was a comparative evaluation study of two screening procedures. Ophthalmologic examinations (N = 70) were performed on 24 infants with both BIO and WFDRI. Pain assessments were performed with two specific neonatal scales (Crying, requires oxygen, increased vital signs, expression and sleeplessness, CRIES and, Premature infant pain profile, PIPP) just prior to the examination, and 30 seconds, 1 hour, and 24 hours later after ending the examination. Results Changes over time were significantly different between BIO and WFDRI with both scales (PIPP score, p = .007, and CRIES score, p = .001). Median PIPP score (interquartile interval) at baseline was 4 (3-5). At 30 seconds the score was 8 (6-9) for BIO and 6 (5-7) for WFDRI, respectively. The increase in PIPP score between baseline and 30 seconds was significantly lower with WFDRI (p = .006). The median increase in CRIES score from baseline to 30 seconds was 1 point lower for WFDRI than for BIO (p < .001). No significant difference in response remained at 1 hour or 24 hour assessments. Conclusions A transient short-term pain and stress response occurs with both BIO and WFDRI. Infants examined for screening of ROP with digital retinal imaging present less pain and stress at 30 seconds following completion of the exam when compared with binocular indirect ophthalmoscopy.